BIMBINGAN PRIBADI-SOSIAL BERBASI ZOOM MEETING UNTUK KONSEP DIRI POSITIF PESERTA DIDIK SMP KELAS IX - Selly Rizky Yuliana; Wahyu Hidayat; Siti Fatimah (IKIP Siliwangi, 2023)
This research is motivated by the existence of a negative self-concept in class IX students. This is indicated by the behavior that is not in accordance with the behavior of students at school. This study uses a qualitative descriptive method with the aim of describing the implementation of pribadi-social guidance. The results of the research obtained in the implementation of pribadi-social guidance using a zoom meeting, namely planning first then carrying out services through several stages such as problems, diagnosis, prognosis, therapy and evaluation and follow-up. This can be seen from inappropriate behaviors such as not liking criticism, withdrawing from friends and not understanding himself, his family, and the people around him. Social interaction is also hampered and makes it difficult for these students to develop their potentialKeywords: Pribadi-Social Guidance, Self-Concept, Zoom Meeting, Learners